2021
DOI: 10.3389/fphar.2021.644129
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclol Regulates Hepatic Gluconeogenesis in Rats with Type 2 Diabetes and Non-alcoholic Fatty Liver Disease by Inhibiting Inflammation

Abstract: Hepatic gluconeogenesis plays an important role in maintaining the body’s glucose metabolism homeostasis. Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver diseases, when combined with type 2 diabetes mellitus (T2DM), it can cause severe glucose metabolism disorders. Studies have confirmed that chronic liver inflammatory lesions are the basis of T2DM combined with NAFLD (T2DM–NAFLD), inhibiting liver inflammation can improve glucose metabolism disorders. It is essential to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The beneficial effects of bicyclol on inflammatory and metabolic diseases have been well documented (Li H et al, 2021). The preclinical reports and clinical studies have demonstrated that bicyclol is a potential agent for NAFLD/NASH treatment (Li et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beneficial effects of bicyclol on inflammatory and metabolic diseases have been well documented (Li H et al, 2021). The preclinical reports and clinical studies have demonstrated that bicyclol is a potential agent for NAFLD/NASH treatment (Li et al, 2020;.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic meta-analysis presented the evidence of bicyclol treatment for improving liver function and serum lipid biomarkers in patients with NAFLD, predicting that bicyclol might be an alternative agent for NAFLD (Li et al, 2020). The quality of evidence suggested that bicyclol administration significantly attenuated high-fat diet (HFD)-induced activation of inflammatory-mediated signaling pathway (MAPKs/NF-κB) and gluconeogenesis/insulin signaling pathway (Akt, PGC-1α and PEPCK) (Li H et al, 2021;Zhao W et al, 2021). Pharmacological studies displayed that bicyclol had obvious protective effects against hepatocyte injury caused by tetracycline, alcoholic and non-alcoholic fatty liver associated with cell apoptosis, endoplasmic reticulum (ER), and oxidative stress (Yao et al, 2016;Jia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Activation of pyruvate to phosphoenolpyruvate is the first step for phosphoenolpyruvate carboxykinase (PEPCK) and glucose-6-phosphate (G6Pase)-mediated gluconeogenesis [ 85 ]. Excessive release of glucose via gluconeogenesis enhances IR-mediated inflammation, steatosis, and de novo lipogenesis in patients with NAFLD [ 86 ]. PGC-1α-activated PEPCK expression induced by HFD-mediated inflammation is suppressed by bicyclol, an approved drug for targeting hepatitis, liver fibrosis, and liver injury [ 86 ].…”
Section: Gluconeogenesismentioning
confidence: 99%
“…Excessive release of glucose via gluconeogenesis enhances IR-mediated inflammation, steatosis, and de novo lipogenesis in patients with NAFLD [ 86 ]. PGC-1α-activated PEPCK expression induced by HFD-mediated inflammation is suppressed by bicyclol, an approved drug for targeting hepatitis, liver fibrosis, and liver injury [ 86 ]. Inactivation of the AMPK-mediated SIRT–PGC1 axis is involved in HFD-fed NASH progression [ 83 ].…”
Section: Gluconeogenesismentioning
confidence: 99%
“…This shows that the two factors play complementary roles in the inflammatory loop of T2DM homoeopathy and together promote the formation of ocular surface inflammation [ 8 ]. TNF- α and IL-1 β are two factors with inflammatory significance in the P38MAPK and PI3K/Akt signaling pathway in T2DM patients with induced T2DM homoeopathy, which can reflect the inflammatory state of the ocular surface [ 9 ]. Our study analyzed the expression of TNF- α and IL-1 β in the peripheral blood of patients with T2DM homoeopathy, aiming to provide more references for the clinical treatment of patients.…”
Section: Introductionmentioning
confidence: 99%